2019
DOI: 10.1111/jgs.16272
|View full text |Cite
|
Sign up to set email alerts
|

Intensive vs Standard Blood Pressure Control in Adults 80 Years or Older: A Secondary Analysis of the Systolic Blood Pressure Intervention Trial

Abstract: OBJECTIVES To evaluate the effect of intensive systolic blood pressure (SBP) control in older adults with hypertension, considering cognitive and physical function. DESIGN Secondary analysis. SETTING Systolic Blood Pressure Intervention Trial (SPRINT) PARTICIPANTS Adults 80 years or older. INTERVENTION Participants with hypertension but without diabetes (N = 1167) were randomized to an SBP target below 120 mm Hg (intensive treatment) vs a target below 140 mm Hg (standard treatment). MEASUREMENTS We measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 39 publications
2
40
0
1
Order By: Relevance
“…After four years, the participants in the intensive blood pressure control group had a smaller increase in cerebral white matter lesions compared to the participants in the standard blood pressure control group [232]. Overall, the SPRINT-MIND trial highlights the potential for early and aggressive blood pressure lowering interventions to have a positive impact on the cerebrovascular health of older adults, which may lower risk of cognitive impairment [228,231,232].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After four years, the participants in the intensive blood pressure control group had a smaller increase in cerebral white matter lesions compared to the participants in the standard blood pressure control group [232]. Overall, the SPRINT-MIND trial highlights the potential for early and aggressive blood pressure lowering interventions to have a positive impact on the cerebrovascular health of older adults, which may lower risk of cognitive impairment [228,231,232].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Intensive blood pressure control in participants over 80 years old was associated with a greater risk of developing hypotension and possibly syncope, but was not associated with a higher risk of falls as compared to the standard blood pressure control group [ 230 ]. In most participants over 80 with at least three co-morbidities, intensive blood pressure control was associated with decreased risk of major cardiovascular events, MCI, and death [ 231 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…However, the authors acknowledged that their findings may not have been statistically adequate, as the study ended prematurely with fewer cases of dementia than expected. Interestingly, a recently published secondary analysis of the Systolic Blood Pressure Intervention Trial showed that for patients aged  80 years with hypertension and no T2DM, intensive SBP control of < 120 mmHg compared to standard SBP control < 140 mmHg lowered the risk of major cardiovascular events, mild cognitive impairment (MCI), and death, with increased risk of changes in kidney function [19]. However, no incidence of dementia was observed.…”
Section: Hypertension Treatment Target Bp and Cognitive Function In The Elderly With Hypertensionmentioning
confidence: 99%
“…Similar proportions of patients were eligible for each trial when the population was limited to those with a previous diagnosis of hypertension, with the exception of OPTiMISE that had more eligible hypertensive patients (35.0%; 95% CI = 34.1-35.9%). a Data relating to the reported populations were extracted from previous publications (HYVET, SPRINT) 3,11 or obtained from the original trial data set (OPTiMISE). 18 Comparisons were made using independent samples t tests and two sample tests of proportions.…”
Section: Primary Resultsmentioning
confidence: 99%